2016
DOI: 10.5935/1984-2295.20160047
|View full text |Cite
|
Sign up to set email alerts
|

Porous space in Brazilian soils using X-ray computed tomography

Abstract: A porosidade é importante na determinação da qualidade de um solo, por possuir forte influência na aeração, na transferência de água/solutos/gases/calor, na resistência à penetração e ramificação de raízes, além do desenvolvimento de microorganismos. A avaliação do espaço poroso, considerando vazios intra e interagregados, em diferentes tipos de solo e suas implicações (vantagens/desvantagens) é objetivo deste estudo. Foi determinada a porosidade inter e intra-agregados em solos dos tipos Latossolo Vermelho di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…3 L-type voids were considered as inter-aggregate voids, while voids classified as M and P were considered as the intraaggregate voids (Costa et al, 2016). Intra-aggregates were classified according to shape, size and inclination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 L-type voids were considered as inter-aggregate voids, while voids classified as M and P were considered as the intraaggregate voids (Costa et al, 2016). Intra-aggregates were classified according to shape, size and inclination.…”
Section: Resultsmentioning
confidence: 99%
“…A variability threshold coefficient of 20% was adopted for voxel intensity, in comparison to the mean, considering as pure those with intensity within the following interval [m -1s, m + 1s] (Costa et al, 2016). These limits were adopted to locate a multimodal histogram, which can be modeled as a mixture of Gaussians.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the pores observed along the sample, it is reported that the interconnected pore volume promotes fluid flow permeability along the structure, as it allows fluid transmission between pores. Although porosity estimation by image analysis generated by computed microtomography has the advantage of being a non-destructive verification [20], pores smaller than the image voxel size (55 µm) were not identified and were no quantified in the total pore volume, being a limitation of this methodology [36]. This graph shows the porosity distribution profile (%) and the slice position along the length of the sample, where 0 on the horizontal axis indicates the center portion of the rock.…”
Section: Chemical/mineralogical Analysesmentioning
confidence: 99%